Systems and methods for producing polymer-carbon nanomaterial blends from carbon dioxide and products thereof

The production of carbanogel through a molten electrolysis process using carbon dioxide addresses the high cost and carbon footprint of CNM manufacturing, enabling efficient and cost-effective distribution of CNMs in polymer mixtures, enhancing their properties and overcoming uniform dispersion challenges.

JP7603176B2Active Publication Date: 2024-12-19DIRECT AIR CAPTURE LLC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023571172
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-24
Filing Date
2022-05-24
Publication Date
2024-12-19
Estimated Expiration
2042-05-24

AI Technical Summary

Technical Problem

The high cost and carbon footprint associated with the commercial manufacturing of polymer-carbon nanomaterial (CNM) mixtures, as well as the challenge of achieving uniform dispersion of CNMs in polymer mixtures, particularly when smaller amounts are present, hinder their widespread use and deployment.

Method used

A method involving the production of carbanogel using a molten electrolysis process that incorporates carbon dioxide to create a lattice-like structure for CNMs, allowing for a more efficient and cost-effective distribution of CNMs within polymer mixtures, reducing manufacturing costs by two orders of magnitude and facilitating uniform dispersion.

Benefits of technology

This approach significantly reduces manufacturing costs and enhances the uniform distribution of CNMs, thereby improving the properties of polymer-CNM mixtures, such as strength, conductivity, and catalytic properties, while minimizing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603176000001
    Figure 0007603176000001
  • Figure 0007603176000002
    Figure 0007603176000002
  • Figure 0007603176000003
    Figure 0007603176000003
Patent Text Reader

Abstract

Embodiments of the present disclosure relate to devices, systems, and methods for making blends of polymers and carbon nanomaterials (CNMs). The blends of such embodiments include up to about 10 weight percent (wt%) CNMs. The CNM content of such blends may impart new or improved properties to the blends as well as materials and products made therefrom. Such new or improved products may include improved tensile strength, new or improved electro-medical, structural thermal, catalytic properties, or any combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to and the benefit of U.S. Provisional Patent Application No. 63 / 192,304, filed May 24, 2021, the entire contents of which are incorporated by reference herein.

[0002]

[0002] The present disclosure relates to the manufacture of products using an electrolysis process. In particular, the present disclosure relates to a method of making a carbanogel mixture product from carbon dioxide split using an electrolysis process. [Background technology]

[0003]

[0003] As of 2015, the annual plastic production can be summarized as follows: Polypropylene (PP) - 68 megatons (MT) of non-fiber PP produced, 52 MT of fiber PP produced, Polyethylene (PE) - 64 MT of low density PE produced, 52 MT of high density PE produced, Polyester also called polyethylene terephthalate (PET) - 33 MT produced per year, Polyvinyl chloride (PVC) - 38 MT produced per year. The production of other plastics is dramatically lower than that of PVC.

[0004]

[0004] During the production of plastics, the polymerization of monomers to form polymers occurs through reactions such as condensation reactions, ring-opening reactions, ionic reactions, chain transfer reactions or plasma polymerization reactions. Polymers are often divided into natural polymers, synthetic polymers, semi-synthetic polymers, recycled polymers, amorphous polymers, semi-crystalline polymers, thermoplastic or thermoset plastics, etc.

[0005]

[0005] The main advantages of PP and PE production are that it is inexpensive and provides plastics with desirable mechanical flexibility. PP and PE are created from high temperature and pressure gases with special catalysts. PP and PE are a challenge to recycle as they are chemically resistant plastics and PP and PE remain in the environment, exacerbating plastic pollution.

[0006]

[0006] PVC is usually made from a coolant, an initiator, and one or more additives to promote the suspension of small PVC particles in water. The aqueous suspension is then dried and dissolved together. Sometimes, PVC particles are produced first and then mixed with plasticizers or other additives in suspension. This polymerization reaction does not create anything more than PVC. Typically, plasticizers and carbonates are added to increase the strength, flexibility of PVC, as well as the speed and ease of PVC production.

[0007]

[0007] Thermoplastics are often associated with materials that require stiffness. Thermoplastics can be melted by heat, cooled to resolidify, and formed to take on various forms via molding, compression molding, machining, or by 3D printing applications. Polylactic acid (PLA) is an example of a thermoplastic that is renewable, can be sourced from living organisms, and can potentially be biodegraded. PLA is relatively easy to create by simple heating, producing water as a by-product. The main limitation of PLA is its low strength properties. Plasticizers are often used as additives to increase desirable properties in PLA, including polycarboxylates or citric acid with many carboxylate groups.

[0008]

[0008] PLA's annual production (2019) was only 0.2 MT, but it has one of the highest annual production growth rates (26%) resulting in demand exceeding supply, driving up prices. As a thermoplastic, PLA is a polymer that can be melted by heat, cooled and shaped, a property it shares with all thermoplastics including, but not limited to, PE, PP, PVC, acrylic, acrylonitrile butadiene styrene, or ABS, nylon, Teflon, and polycarbonate, or PC. ABS is a plastic commonly used for 3D printing applications, and ABS is also used in car bodies, appliances and phone cases.

[0009]

[0009] In contrast, thermosetting resins are irreversibly cured to a permanent solid state via a crosslinker and formed by a chemical reaction. For example, thermosetting resins can also be used for printing in 3D printing applications only via a chemical reaction, such as, but not limited to, photopolymerization or thermal chemical reaction. Before curing, one or more pre-cured components of a thermosetting resin are available as a liquid, which is often viscous or dense. Thermosetting resins are often more resistant to high temperatures and tend to decompose rather than dissolve at high temperatures. Common examples of thermosetting resins include epoxy (and epoxy resins), acrylic, phenolic, silicone (polysiloxane), polyurethane (PU), polyimide, vulcanized rubber, bakelite (polyoxybenzyl methylene glycol anhydride), polydicyclopentadiene (pDCPD), polyisocyanurate, polyester, polyurea, urea formaldehyde, and vinyl ester, cyanate, melamine, or polyester resins.

[0010]

[0010] Carbon nanomaterials (CNMs), including carbon nanotubes (CNTs), are added to plastics to form admixtures, also referred to herein as admixtures, and composites and products can be made from such admixtures. Historically, PVC-CNT and PLA-CNT admixtures were made by either dissolving the plastic in a solvent, dispersing the CNTs therein by sonication, and then drying the admixture, or by dissolving plastic beads mixed with the CNTs.

[0011]

[0011] Polymer-CNT blends have been investigated using other polymers including PLA, PVC and polyurethanes, polystyrene, polyaniline, polyvinylidene fluoride and a wide range of epoxies, including printed PLA / CNT components. Blends of graphene and graphene oxide polymers are also known.

[0012]

[0012] Kevlar is neither a thermoset nor a thermoplastic, since it is formed by spinning a solution of the polymer into the fiber. Kevlar-CNT composites are formed by coating Kevlar onto CNTs and grafting the CNTs with repeating units of the polymers p-phenylene terephthalamide (PPPA) and terephthaloyl chloride (TPC) covalently bonded to the surface of the CNTs. Kevlar-CNT blends can significantly increase their impact resistance. The normalized absorbed energy increased by 6.5 times with the addition of 0.1 weight percent (wt%) CNTs compared to no CNTs.

[0013]

[0013] Although it is known to combine CNMs and polymers to impart a number of new and improved properties to the resulting material or product, the use and deployment of such resulting materials and products has not been widespread. Without being limited by any particular theory, this hindered use and deployment may be due to the common methods of making CNM components, which are expensive and have a high associated carbon footprint. For example, chemical vapor deposition (CVD) is a process traditionally used in the commercial manufacture of CNMs. CVD is expensive, and currently, the price of CNMs, such as CNTs, graphene, and carbon nano-onions, ranges from $100,000 to $10,000,000 per ton. In comparison, steel has a price of $400 to $700 per ton.

[0014]

[0014] Therefore, new approaches to the commercial production of polymer-CNM blends and materials and products made therefrom that address the high costs and associated high carbon footprint are desirable. Summary of the Invention

[0015]

[0015] Embodiments of the present disclosure relate to polymer-carbon nanomaterial (CNM) blends that can be used to create materials or products that have new or improved properties compared to materials or products made from polymers alone.

[0016] Some embodiments of the present disclosure relate to a method of making a polymer-CNM mixture, the method including receiving a carbanogel, combining the carbanogel with a polymer mixture, and collecting (also referred to as recovering) the polymer-CNM mixture.

[0017] Some embodiments of the present disclosure relate to polymer-CNM mixtures and polymer mixtures that include carbanogels.

[0018] Some embodiments of the present disclosure relate to a system for making a polymer-CNM mixture, the system including an apparatus for performing an electrolysis process of splitting carbon dioxide (CO2) in a molten electrolyte to produce a carbanogel, the carbanogel including carbon nanomaterials (CNMs) and an electrolyte, a container for receiving the carbanogel, and a source of a polymer mixture.

[0019]

[0019] The development of polymer-CNM blends and the resulting composites has been hampered by the expense of producing the CNM component and the associated high carbon footprint. Furthermore, technical challenges exist for establishing a uniform distribution of CNM throughout the blend, especially when smaller amounts of CNM are present.

[0020]

[0020] It is known that the high manufacturing costs of CNMs are mainly due to high reactant and energy costs. Without being limited by any particular theory, these manufacturing costs can be reduced by two orders of magnitude when produced from CO2 using a melt electrolysis process and the produced CNMs can be used as components in the polymer-CNM mixture according to the embodiments of the present disclosure. Furthermore, without being limited by any particular theory, the carbanogel produced by the electrolysis process can also help overcome the challenge of establishing a uniform distribution of CNMs throughout the mixture by the carbanogel providing a lattice-like structure that can provide fixed and distributed locations for CNMs. [Brief description of the drawings]

[0021]

[0021] These and other features of the present disclosure will become more apparent from the following detailed description, which refers to the accompanying drawings.

[0022] [Figure 1] 1 is a schematic diagram of an apparatus for making a carbanogel product for use in an embodiment of the present disclosure. [Diagram 2]

[0023] FIG. 1 is a schematic diagram of a system according to an embodiment of the present disclosure for making a polymer-CNM mixture. [Diagram 3]

[0024] 1 is a schematic diagram illustrating steps of a method according to an embodiment of the present disclosure. [Figure 4]

[0025] It has two panels showing properties of embodiments of the present disclosure, the top panel shows photographs of epoxy resin items made with and without carbanogel, and the bottom panel is a bar graph showing increased tensile strength versus weight % addition of carbanogel. [Figure 5A]

[0026] 1 shows a photograph of a scanning electron microscope image of a carbanogel made according to an embodiment of the present disclosure, the image being shown at 730x magnification. [Figure 5B]

[0026] Figure 1 shows a photograph of a scanning electron microscope image of a carbanogel made according to an embodiment of the present disclosure, showing an image at 8600x magnification. [Figure 6]

[0027] FIG. 1 has two panels showing schematic diagrams of additional protocols for making polymer-CNM mixtures according to embodiments of the present disclosure, the top panel showing a protocol in which the combining step occurs prior to preparing the polymer, and the bottom panel showing a protocol in which the combining step occurs subsequent to preparing the polymer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023]

[0028] The embodiments of the present disclosure relate to devices, systems, and methods for making blends of polymers and carbon nanomaterials (CNMs). The blends of such embodiments include up to about 10 weight percent (wt%) CNMs. The CNM content of such blends may impart new or improved properties to the blends and materials and products made therefrom. Such new or improved properties include, but are not limited to, strength properties, properties for electronic applications, properties for medical applications, thermal conductivity properties, thermal insulation properties, catalytic properties, or any combination thereof.

[0024]

[0029] Since 2009, the energy efficient conversion of CO2 to carbon and oxidation by molten carbonate electrolysis has been known. Subsequently, the chemical conversion of CO2 to various graphitic carbon nanomaterials (CNMs) has been demonstrated. These graphitic CNMs are valuable due to their long-term stability and the useful properties that these materials possess, such as ultra-high strength, high electrical and thermal conductivity, new electronics, high battery, fuel cell and capacitor storage capacity, electromagnetic radiation shielding, effective drug delivery and various medical properties, as well as useful catalytic properties. CO2→C ナノ物質 +O2 (formula 1)

[0025]

[0030] Equation 1 shows the melt electrolysis process, where carbon nanomaterials grow and remain on the cathode as a mixture of entangled CNMs mixed with electrolyte. This mixture is called a carbanogel, and at least 95% of the electrolyte can be extruded from the carbanogel by hot press filtration.

[0026]

[0031] Graphene sp , which may occur within the CNM component 2The inclusion of bound carbon components and single or multi-layer graphene may provide improved properties to the CNMs in the carbanogel, such as, but not limited to, enhanced strength and conductivity of these CNMs. Additionally, the relative amounts of certain morphologies of CNMs may impart additional properties to the carbanogel and products made therefrom. Examples of such morphologies include, but are not limited to, spherical nanocarbons, solid and hollow nano-onions, cylindrical allotropes of nanocarbons, planar allotropes, helical allotropes, carbon nanotubes (CNTs), nanofibers, graphene, nanoplatelets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface-modified or metal-coated CNMs, amorphous nanocarbons without geometrical features or characteristics, or any combination thereof. Examples of such additional properties include, but are not limited to, reduced friction, elasticity, thermal conductivity, flame retardancy, chirality, enhanced surface area, or any combination thereof, of the CNMs in the carbanogel. These properties are useful for certain applications including, but not limited to, lubrication, flexible materials, chiral light absorption, chiral light emission, chiral catalysis, improved electrochemical charge storage, improved catalytic activity, fire resistance, or enhanced EMF shielding capabilities. The CNMs in the carbanogel may also include additional features including doping, magnetism, unusual shapes, and miniaturized or enlarged sizes. Without being bound by any theory, the CNTs may be single-walled CNTs, multi-walled CNTs, doped CNTs, such as boron, sulfur, phosphorus or nitrogen doped CNTs, magnetic CNTs, bamboo-shaped CNTs, pearl-shaped CNTs, isotopically specific CNTs, such as 12 C and 13 The CNTs may include CCNTs, surface modified or metallized CNTs, helical CNTs including single or double braided CNTs, spiral helical CNTs, thin, thick or solid wall CNTs, small and large diameter CNTs, short or woolly (long) CNTs, or any combination thereof.

[0027]

[0032] According to embodiments of the present disclosure, a carbon-containing gas may undergo an electrolysis process, also referred to herein as an electrosynthesis process, to generate a carbanogel comprising a carbon nanomaterial (CNM) product from the carbon in the gas. The term "carbanogel" is used herein to refer to a mixture of CNMs and electrolyte that is a product of the electrolysis process and is localized at the cathode during or after the electrolysis process. The terms "carbon nanomaterial product" and "CNM product" are used herein to refer to a collection of nanocarbon, which may also be referred to as nanoscale carbon, in one or more forms. The term "nanocarbon" is used herein to refer to carbon arranged at the nanoscale in specific structures, e.g., graphitic nanocarbon structures. In particular, carbon from a carbon-containing gas may be split into carbon and oxygen using a molten electrolyte medium and various electrolysis process configurations. The electrolysis process may cause mass transfer of carbon from the gas phase to the molten electrolyte medium, the solid CNM product, or both. The CNM product may be substantially pure, pure, or impure carbon nanomaterial (CNM) including carbon nanotubes (CNTs). The CNM product may include one or more forms of CNM structures as described hereinabove, or any combination thereof. Optionally, one or more parameters of the electrolysis process may be adjusted to vary the relative amounts of a given form in the CNM product.

[0028]

[0033] As shown in FIG. 1, the electrolysis process may take place in an apparatus 10 including a case 12, which may be referred to as an electrolysis chamber or electrolysis cell, for housing a cathode 18, and an anode 16 may form at least a portion of the inner surface of the wall of the case 12. Together, the two electrodes define an electrolysis space between them. Optionally, the anode 16 may be separate from the wall of the case 12, as will be appreciated by those skilled in the art. The case 12 is configured to house an electrolyte medium 21. The electrolysis space B, including the top surface 21A of the electrolyte, may be in fluid communication with a carbon-containing gas source (shown as D in FIG. 1). In some embodiments of the present disclosure, the case 12 may be contained within an insulated housing 20 made of a thermal insulating material. The insulated housing 20 may also include a top 22 or sides or bottom (not shown) made of a thermal insulating material or not, and the thermal insulating material may be derived from a CO2-permeable insulating material, such as a high-temperature woven ceramic or a substantially CO2-impermeable insulating material. Examples of permeable insulation materials include, but are not limited to, Morgan Cerablanket®, made from oxides of alumina and silica and may contain zirconia, and Morgan Superwool®, made from alkaline earth silicates, both rated for temperatures above 1,200° C. Examples of substantially CO2 impermeable insulation materials include the wide range of commercially available firebricks or cast-in-place refractory cements and mortars, examples of which include, but are not limited to, BNZ Materials firebricks and refractory cements and mortars rated for temperatures above 1,090° C., such as PA20 and 23, and BNZ2000, 2300, 23A, 2600, 26-60, 2800, 3000 and 3200.

[0029]

[0034] The carbon-containing gas source may be various industrial plants including, but not limited to, cement manufacturing plants, iron refining plants, steel manufacturing plants, plants that make or use one or more of ammonia, ethanol, magnesium, hydrogen, polymers, plastics, glass, wastewater treatment plants, food processing plants. The carbon-containing gas source may also be a chemical reactor, including internal combustion engines and the combustion of carbonaceous materials for heating or cooking. Exhaust gas from power plants, steam generation facilities, or pyrolysis reactors may also be carbon-containing gas sources. Carbon-containing gases emitted from these sources or in the manufacture of any high carbon footprint material may also contribute to or constitute the carbon source for making the CNM product. Additionally, gas products and carbon products of the combustion or conversion of fossil fuels for heating, transportation, such as polymers and plastics, may also contribute to or constitute the carbon source for making the CNM product.

[0030]

[0035] In some embodiments of the present disclosure, the anode 16 may be formed as a planar structure, a wire structure, a screen, a porous structure, a conductive plate, a flat or folded shim, a coiled structure, or the anode may form at least a portion of the inner wall of the case 12. The anode 16 may be formed of a variety of conductive materials such that the anode 16 may or may not be oxygen evolving. Such anode forming materials include, but are not limited to, any conductive material that has or establishes a stable layer, Ni, Ni alloys, galvanized (zinc coated) steel, titanium, graphite, iron, and a wide variety of metals that establish a highly stable oxide outer layer that promotes oxygen production during the electrolysis reaction carried out by embodiments of the present disclosure. Further examples of suitable materials for forming the anode 16 include nickel alloy 36 (nickel without chromium but with iron), stainless steels such as SS304 or SS316, Nichromes (nickel-chromium based alloys), and Inconel alloys such as Inconel 600, 625 and 718, alloy C-264 or Nichromes such as Chromel A, B or, as co-nucleation of the alloying components is known to produce high quality CNTs. Binary and ternary transition metal nucleating agents including, but not limited to, Ni, Cr, Sn, In, Fe and Mo may also be useful and may affect the growth of the CNM product as well.

[0031]

[0036] In some embodiments of the present disclosure, a transition metal may be added to the anode 16, which may be dissolved from the anode 16 to migrate through the electrolyte medium 21 to the cathode 18. The added transition metal may function as a nucleating agent, which may be selected from nickel, iron, cobalt, copper, titanium, chromium, manganese, zirconium, molybdenum, silver, cadmium, tin, ruthenium, zinc, antimony, vanadium tungsten, indium, gallium, or non-transition metals such as germanium or silicon or mixtures thereof, including but not limited to brass, monel, and nickel alloys. The transition metal may also be directly introduced as a transition metal salt dissolved in the electrolyte medium 21 to migrate onto the cathode 18. It is also possible to add the transition metal nucleating agent directly onto the cathode 18.

[0032]

[0037] In some embodiments of the present disclosure, the cathode 18 may be formed as a planar structure, a wire structure, a screen, a porous structure, a conductive plate, a flat or folded shim, a sheet, a coiled structure, or the cathode may form at least a portion of the inner wall of the case 12. The cathode 18 may be formed of a variety of conductive materials reflecting the need for nucleation points and variations in the CNM products that form on the cathode 18. Such cathode forming materials include, but are not limited to, any conductive material, galvanized (zinc coated) steel, titanium, graphite, iron, alloys including copper and zinc, Monel (Ni400, Ni / Cu alloy), Inconel, stainless steel, iron, nichrome, pure Cu, and brass alloys may also be suitable materials for making the cathode 18.

[0033]

[0038] The anode 16 and the cathode 18 may be aligned substantially parallel to each other within the case 12, such as a stainless steel case or a case made of substantially pure or pure alumina. The case 12 may be made of any material suitable for containing the molten electrolyte medium 21 and maintaining the temperature achieved by the device 10A. The electrodes may be oriented in any orientation, including but not limited to substantially horizontal or substantially vertical, but are spaced apart from each other to define an electrolysis space B therebetween. In some embodiments of the present disclosure, the electrolysis space B is about 0.1 cm to about 10 cm. In some embodiments of the present disclosure, the electrolysis space B is about 1 cm. As will be appreciated by those skilled in the art, the dimensions of the electrolysis space B depend on the scale of the device 10, such as the size of each electrode, the plenum defined within the case, the amount of current applied, and combinations thereof.

[0034]

[0039] The anode 16 and the cathode 18 are operably connected to a current source (not shown), which may be any source of AC or DC, either constant or not, that provides a current density of about 0.001 A / cm2 to 10 A / cm2. In some embodiments of the present disclosure, the current density provided between the electrodes is at least 0.02 A / cm2.2 , 0.05A / cm 2 , 0.1A / cm 2 , 0.2A / cm 2 , 0.3A / cm 2 , 0.4A / cm 2 , 0.5A / cm 2 , 0.6A / cm 2 , 0.7A / cm 2 , 0.8A / cm 2 , 0.9A / cm 2 , 1.0A / cm 2 The power for the current source can be any source or combination of sources including mains, solar power, and the like.

[0035]

[0040] The heat source (not shown) can be any heat source that raises the temperature within the case 12 to a temperature that transitions the electrolyte medium 21 into a molten phase. For example, the heat source can achieve a temperature within the case 12 of about 500°C to about 850°C or greater. In some embodiments of the present disclosure, the heating achieves a temperature of about 700°C to about 800°C, about 720°C to about 790°C, or about 750°C to about 780°C. In some embodiments of the present disclosure, the heating achieves a temperature of 749-750°C, 751-752°C, 753-754°C, 755-756°C, 757-758°C, 759-760°C, 761-762°C, 763-764°C, 765-766°C, 767-768°C, 769-770°C, 771-772°C, 773-774°C, 775-776°C, 777-778°C, or 779-780°C. In some embodiments of the present disclosure, the temperature within the case 12 can be increased to about 800°C or higher. In some embodiments of the present disclosure, the heat source is provided or supplemented by the exothermic reaction of CO2 absorption and conversion to carbonate (mass transfer from gas phase to solid phase CNM product) or by the overpotential of the applied electrolysis current.

[0036]

[0041] In some embodiments of the present disclosure, the electrolyte medium may include a carbonate that can be heated by a heat source until it transitions to a molten phase. For example, the carbonate may be lithium carbonate or a lithiated carbonate. Molten carbonates such as lithium carbonate (Li2CO3) with a melting point of 723°C or lower melting point carbonates such as LiBaCaCO3 with a melting point of 620°C, if they include oxides, include spontaneous oxide formation that occurs upon melting or is the result of electrolysis, or when mixed with highly soluble oxides such as Li2O, Na2O, and BaO, sustain rapid absorption of CO2 from the space above the molten electrolyte medium. Suitable carbonates may include alkali carbonates and alkaline earth carbonates. Alkaline carbonates may include lithium, sodium, potassium, rubidium, cesium, or francium carbonates or mixtures thereof. Alkaline earth carbonates may include beryllium, magnesium, calcium, strontium, barium, or radium carbonates or mixtures thereof. In some embodiments of the present disclosure, the electrolyte may be a mixed composition, such as a mixture of one or more of alkali and alkaline earth carbonates and oxides, borates, sulfates, nitrates, chlorides, chlorates, or phosphates.

[0037]

[0042] According to an embodiment of the present disclosure, the carbanogel is formed by molten carbonate electrolysis partitioning of CO2. The carbanogel comprises a mixture of CNM network and electrolyte that remains after the electrolysis process has stopped. Interestingly, after processing such as fracturing, the carbanogel may maintain the CNM network. Furthermore, the electrolyte content of the carbanogel (treated or untreated) may be reduced by pressing, reacting or washing away the electrolyte. After removal of some or all of the electrolyte, the carbanogel consists of a CNM composed of high purity carbon. After removal of some or all of the electrolyte, the CNM defines an internal void. For example, the CNM may define void spaces in the CNM, on the CNM surface and within the CNM, or a combination thereof. For purposes of this disclosure, the term "void" refers to a two-dimensional or three-dimensional space in the CNM that is substantially free of electrolyte or other materials.

[0038]

[0043] In some embodiments of the present disclosure, the voids defined in the CNMs may be partially, substantially completely or completely filled with a void-filling agent, such as a material based on the application. Examples of suitable void-filling agents include, but are not limited to, toughening agents, catalysts, dopants, drugs or electromagnetic field (EMF) shielding agents. Toughening agents may include, but are not limited to, epoxy resins, resins and other polymers, cementitious materials and metals. Catalysts may include, but are not limited to, materials for speeding up chemical or electrochemical reactions. Dopants may include, but are not limited to, materials that substantially affect the physical and chemical properties of the polymer-CNM mixture and materials and products made therefrom in small amounts within the voids. The CNM components in the carbanogel may be mechanically, electrically or magnetically aligned to further enhance or impart new properties to one or more properties of the polymer-CNM mixture and materials and products made therefrom. Such properties include, but are not limited to, strength, electrical and thermal properties. Electrical and / or magnetic alignment may be achieved by applying an orienting electric and / or magnetic field during the carbanogel preparation stage. Magnetic CNMs are prepared by incorporating a magnetic material, such as a metal or metal carbide, during the electrolysis process when generating the CNM. The polymer-CNM mixtures can be used to form sheet materials that can be used alone or in combination with other materials, such as, for example, but not limited to, laminates not made of the polymer-CNM mixtures, in, for example, backings, fire retardants, or shielding, to impart enhanced properties to those other materials.

[0039]

[0044] It is known that the high production costs of CNM are primarily due to high reactant and energy costs. Without being limited by any particular theory, when produced from CO2 using a melt electrolysis process according to embodiments of the present disclosure, these production costs can be reduced by two orders of magnitude.

[0040]

[0045] Some embodiments of the present disclosure relate to a system 200 for making a polymer-CNM mixture 222. As shown in the non-limiting example of Figure 2, the system 200 includes an apparatus 210 for performing an electrolysis process to split carbon dioxide (CO2) in a molten electrolyte to produce a carbanogel product, a vessel 212, and a source of monomer / polymer mixture 214. The system 200 can be used to practice the methods of the present disclosure as described herein below.

[0041]

[0046] In some embodiments of the present disclosure, the apparatus 210 can be the same as or similar to the apparatus 10 described herein above. The apparatus 210 is configured to perform an electrolysis process that splits a carbon-containing gas in a molten electrolyte. The product of that splitting is a CNM product, or carbanogel, which may also be referred to as a carbanogel product, with bulk or residual electrolyte therein.

[0042]

[0047] A container 212 that receives the carbanogel (represented by line X in FIG. 2), whether as a cold product or a hot product. The container 212 can be made of a variety of materials and can be of any shape and size, so long as the container 212 is robust enough to withstand the temperature of the carbanogel received therein.

[0043]

[0048] System 200 may further include an insulation unit 224 for protecting polymer-CNM mixture 222 from an oxidizing environment. Isolation unit 224 may include a suitably sized fluid seal to receive polymer-CNM mixture 222, remove any oxidizing agent, such as an oxygen-containing gas, from within the vessel, for example by a vacuum pump, and replace the fluid within the vessel with a non-oxygen-containing gas, such as an inert gas.

[0044]

[0049] The monomer / polymer mixture source 214 may be a vessel that contains the monomer / polymer mixture, and / or the source 214 may include a preparation unit for preparing the monomer / polymer mixture. For purposes of this disclosure, the term "polymer mixture" is used interchangeably with the terms "polymer mixture," "monomer / polymer mixture," and "monomer / polymer mixture" to refer to a mixture of polymers, homopolymers, heteropolymers, at least two polymers, monomers, at least two monomers, or polymer mixtures, any combination thereof that may be utilized in embodiments of the present disclosure to create a polymer-CNM mixture. For example, the preparation unit may include a reactor in which one or more chemical reactions may occur. Non-limiting examples of such chemical reactions that may occur in the reactor include, but are not limited to, initiation reactions, propagation reactions, termination reactions, condensation reactions, ring-opening reactions, ionic reactions, chain transfer reactions, photon-based reactions, thermal reactions, plasma polymerization reactions, or any combination thereof.

[0045]

[0050] Additionally or alternatively, the preparation unit may include an extruder for applying a predetermined heat and pressure to the extruder input for producing the monomer / polymer mixture.

[0046]

[0051] The source of monomer / polymer mixture 214 may include monomer precursors that may need to be combined with a carbanogel before being prepared into a polymer to produce a polymer-CNM mixture. Additionally or alternatively, the monomer / polymer mixture 214 may include already prepared polymers that can be combined with a carbanogel to produce a polymer-CNM mixture.

[0047]

[0052] In some embodiments of the present disclosure, source 214 is a source of a natural polymer, a synthetic polymer, a semi-synthetic polymer, a recycled polymer, an amorphous polymer, a semi-crystalline polymer, a thermoset polymer, a thermosetting polymer, a thermoplastic polymer, a monomer precursor of such a polymer, or any combination thereof.

[0048]

[0053] In some embodiments of the present disclosure, source 214 is a source of PLA, PVA, PP, PE, acrylic, ABS, nylon, Teflon, PC, epoxy, epoxy, acrylic, phenolic, polysiloxane, polyurethane, polyimide, vulcanized rubber, bakelite, pDCPD, polyisocyanurate, polyester, polyurea, urea formaldehyde, vinyl ester, cyanate, melamine, polyester resins, monomer precursors of such polymers, or any combination thereof.

[0049]

[0054] In some embodiments of the present disclosure, the system 200 may further include a processing unit 216 for crushing the cooled or hot carbanogel product prior to (or after) receipt by the container 212. The processing unit 216 may be any suitable component, mechanism or machine capable of withstanding the temperatures of the carbanogel, such as, but not limited to, a grinder, a comminuting unit, a physical press, a pulverizing unit, a mill, or any combination thereof. The resulting particle size of the carbanogel is determined by the extent of the processing operations performed by the processing unit 216.

[0050]

[0055] In some embodiments of the present disclosure, the system 200 may further include an electrolyte reduction unit 218. The electrolyte reduction unit 218 may receive the cooled or hot carbanogel product directly from the apparatus 210 and / or it may receive the treated carbanogel product from the processing unit 216. The electrolyte reduction unit 218 reduces the electrolyte content of the carbanogel product (treated or untreated) such that the carbanogel with reduced electrolyte content may be processed (or further processed) in the processing unit 216 and then received in the container 212. Alternatively or additionally, the carbanogel with reduced electrolyte content may be received in the container from the electrolyte reduction unit 218.

[0051]

[0056] The electrolyte reduction unit 218 may reduce the electrolyte content of the carbanogel (treated or untreated) by mechanical, chemical, electrochemical, or any combination thereof. For example, the mechanical methods may include various suitable components, mechanisms, or machines that may reduce the electrolyte content of the carbanogel, such as a mechanical press that pushes the carbanogel through a mesh or sieve, a heater to dissolve the electrolyte in the carbanogel, a filter (room temperature or high temperature), or any combination thereof. The chemical methods for reducing the electrolyte content of the carbanogel include one or more washing stations for exposing the carbanogel to one or more chemicals that may dissolve the electrolyte. In addition to reducing the electrolyte content, one or more chemicals may also be added to dissolve impurities such as amorphous carbon or metals from the CNMs in the carbanogel. The electrochemical methods include an apparatus for performing selective electrolysis to reduce the electrolyte content and / or impurity content of the carbanogel.

[0052]

[0057] In some embodiments of the present disclosure, the system 200 may further include an alignment unit 220 for aligning at least a portion of the CNM components in the carbanogel (treated and / or electrolyte-reduced or not) and / or polymer-CNM mixture (as shown in the non-limiting example of FIG. 2). The alignment unit 220 may be integrated into the container 212 such that the alignment procedure performed by the alignment unit 220 is performed within the container 212 mold. Alternatively or additionally, the alignment unit 220 may be a separate physical component from the container 212 that can receive the uncompressed carbanogel (treated and / or electrolyte-reduced or not), perform the alignment procedure, and then transfer the aligned carbanogel to the container 212. The alignment unit 220 may use one or more of mechanical, electrical, magnetic, or any combination thereof, such that the aligned CNM components in the polymer-CNM mixture have the required anisotropic properties. The alignment unit 220 may use a mechanical approach with various suitable components, mechanisms, or machines that can apply an orienting physical stress field to the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or polymer-CNM mixture. For example, the mechanical approach may apply a shear force to the CNM product in the carbanogel. The shear force may be applied by pulling, rotating, or pulling a body, such as a piston, through the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or polymer-CNM mixture. Alternatively, the shear force is applied directly to increase CNM entanglement rather than CNM alignment.

[0053]

[0058] The alignment unit 220 may use an electrical approach via a variety of suitable components, mechanisms, or machines that can apply an orienting electric field to the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or polymer-CNM mixture.

[0054]

[0059] The alignment unit 220 may use a magnetic approach by various suitable components, mechanisms, or machines that can apply an orienting magnetic field to the CNMs (treated and / or electrolyte reduced or not) in the carbanogel and / or polymer-CNM mixture.

[0055]

[0060] In some embodiments of the present disclosure, alignment unit 220 may be used to reduce rather than increase the directional alignment of CNMs, thus reducing any anisotropic properties of the polymer-CNM mixture.

[0056]

[0061] 3 illustrates the steps of a method 100 of making a polymer-CNM mixture as including receiving 102 the carbanogel, combining 108 the carbanogel and the monomer / polymer mixture in a container, and recovering 110 the polymer-CNM mixture. Optionally, method 100 may further include generating 101 the carbanogel by an electrolysis process as described herein above. Method 100 may further include processing 103 and / or reducing 105 the electrolyte content of the carbanogel.

[0057]

[0062] For the receiving step 102, the carbanogel may be generated using the electrolysis process described herein above, which may be referred to as the generating step 101. The generated carbanogel comprises the entangled product of CNMs grown at the cathode during the molten electrolysis splitting of CO2. By selectively controlling the operating parameters of the electrolysis process described above for generating step 101, the generated carbanogel may have a greater relative amount of the desired morphology of CNMs in the carbanogel. For example, the electrolysis process may be controlled to increase the relative amount of spherical nanocarbons, solid and hollow nano-onions, nanocarbons of cylindrical allotropes, planar allotropes, helical allotropes, carbon nanotubes (CNTs), nanofibers, graphene, nanoplatelets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanotrees, nanorods, surface modified or metal coated CNMs, amorphous nanocarbons without geometrical features or characteristics, or any combination thereof, as compared to other morphologies of nanocarbon structures within the CNMs of the carbanogel.

[0058]

[0063] The emerging carbanogel containing the CNM product may be received in a carbanogel processing step 103, which may include cooling the carbanogel, allowing it to peel or breaking off pieces of the carbanogel from the cooled cathode 18, crushing the carbanogel, or any combination thereof. Alternatively, in the processing step 103, the carbanogel containing the CNM product may be extracted from the cathode 18 while still hot and containing hot molten electrolyte, and then subjected to crushing the hot carbanogel or other steps of the method described herein. Thus, the receiving step 102 may be of a cooled and solid or hot and viscous fluid carbanogel, which may or may not undergo further processing.

[0059]

[0064] According to embodiments of the present disclosure, the processing step 103 can be performed in various manners, such as crushing techniques, including but not limited to grinding, comminuting, pressing, pulverizing, milling, or combinations thereof. The resulting particle size of the carbanogel material in the carbanogel is determined by the degree of crushing. Further and / or more severe crushing results in smaller carbanogel particle sizes, which may affect the combination of the polymer mixture and the carbanogel, compared to scenarios in which the processing step 103 is performed for a shorter time and / or with less severity.

[0060]

[0065] In some embodiments of the present disclosure, the electrolyte and / or impurity content of the carbanogel may be reduced by the reducing step 105. Without being limited thereto, the reduced impurities may include non-graphitic carbon, such as amorphous carbon, and metals, or combinations thereof. Some, most, substantially all, or all of the electrolyte and / or impurities may be removed from the carbanogel by pressing, reacting, or washing the carbanogel in a chemical, mechanical, or electrochemical manner. For example, the mechanical manner for the reducing step 105 may include applying physical pressure to the carbanogel to physically force the electrolyte out of the carbanogel through a sorting device, such as a mesh with a specific pore size. The mechanical manner may also include adjusting the temperature above the melting point of the electrolyte to facilitate electrolyte flow and separation. The melting points of the alkali and alkaline earth carbonate electrolytes range from less than 400° C. for molten ternary eutectic Li, Na, K carbonates to 891° C. for potassium carbonates. The applied pressure may range from 0 to 1000 pounds per square inch (psi), 1000 to 2000 psi, or may be 2000 psi or greater. Alternatively or additionally, reducing 105 may include chemical methods, where the carbanogel is exposed to one or more chemicals to cause a reaction that reduces the electrolyte content of the carbanogel. For example, a washing solution may be used to wash the carbanogel, where the washing solution may dissolve some of the residual or bulk electrolyte from the carbanogel particles. The washing solution may include a neutral pH liquid, such as water or a saline solution, or an acidic or alkaline solution that may facilitate dissolution of the molten electrolyte, such as formic acid or hydrochloric acid or ammonia sulfate, an oxidizing solution, such as permagnate or peroxide, or an organic solvent, or any combination thereof. In addition to reducing the electrolyte, the washing solution may be applied to dissolve impurities, such as amorphous carbon or metals, from the CNM. In some embodiments of the present disclosure, the electrolyte content of the carbanogel may be reduced by room temperature filtration and / or high temperature filtration.Further methods for reducing the electrolyte content of the carbanogel 105 include, but are not limited to, mechanical methods such as sieving and filtering, electrochemical means such as selective electrolysis, thermal means such as oxidative removal by burning of less stable amorphous carbon are applied to remove CNM impurities, or any combination thereof. Reducing the electrolyte content of the carbanogel may increase the relative proportion of CNMs in the carbanogel. In some embodiments of the present disclosure, the step 105 of reducing the electrolyte and / or impurity content of the carbanogel may be performed once or more than once on treated or untreated carbanogels.

[0061]

[0066] In one embodiment of the present disclosure, the carbanogel (treated and / or with or without reduced electrolyte content) is combined with the polymer mixture in a single step to form a polymer-CNM mixture. In another embodiment, the carbanogel (treated and / or with or without reduced electrolyte content) is added during a step of preparing the polymer, such as during the initiation step, and / or the propagation step, and / or the termination step of preparing the polymer. In another embodiment, the carbanogel (treated and / or with or without reduced electrolyte content) is added during a step of preparing the polymer where a condensation reaction / mechanism occurs, a ring-opening reaction / mechanism occurs, an ionic reaction / mechanism occurs, a chain transfer reaction / mechanism occurs, a photon-based reaction / mechanism occurs, a thermal reaction / mechanism occurs, a chemical reaction / mechanism occurs, a plasma polymerization reaction / mechanism occurs, or a combination thereof.

[0062]

[0067] In some embodiments of the present disclosure, the carbanogel (treated and / or with or without reduced electrolyte content) is added during the preparation of natural, synthetic, semi-synthetic or regenerated polymers. In another embodiment of the present disclosure, the carbanogel (treated and / or with or without reduced electrolyte content) is added during the preparation of thermoplastic or thermosetting polymers. In another embodiment of the present disclosure, the carbanogel (treated and / or with or without reduced electrolyte content) is added during the formation of amorphous or semi-crystalline polymers.

[0063]

[0068] Without being limited by any particular theory, the inventors theorize that the fused residual electrolyte within the treated carbanogel particles provides the driving force for uniform distribution of CNMs, binding the treated carbanogel particles to the polymer-CNM mixture after combination without the need for sonication or other more rigorous mixing processes. The carbanogel prepared during the electrolysis process to split CO2 contains both CNMs and electrolyte, and this combined presence may provide a fixed structure that is effectively a lattice matrix of "pre-dispersed" CNMs. EXAMPLES

[0064]

[0069] Example 1: Carbanogel PLA polymer-CNT formation conditions by polymerization

[0065]

[0070] Some embodiments of the present disclosure relate to a method for preparing a polymer-CNT mixture, where the polymer mixture comprises PLA. In this method, the carbanogel is treated by crushing to form carbanogel particles that are added prior to the polymerization step, then proceeding to form a mixture of PLA polymer and CNMs of the crushed carbanogel. Conventional polymerization preparation of PLA proceeds by one of two routes: condensation (also called direct) polymerization or ring-opening condensation polymerization (also called open loop). For example, an aqueous lactic acid solution can be heated and vacuum pumped alone or in the presence of a catalyst to remove water. Once the reaction is complete or nearly complete, the liquid PLA (which dissolves at about 130-180°C) can be drained or stored for later use as a solid. Either PLA preparation route can provide an initiation and / or propagation and / or termination step of the crushed carbanogel of PLA formation, for example, by adding CNMs (of the crushed carbanogel) to form a PLA-CNM mixture.

[0066]

[0071] CNTs are the strongest material known and greatly improve the strength of PLA-CNT blends compared to PLA alone. Typically, CNTs are not added to thermoplastics prior to polymerization, but rather with sonication and / or dissolved thermoplastic solvent mixtures to allow uniform distribution of CNTs, or with extensive mixing during melting prior to extrusion. Instead, as an example of this embodiment, CNTs are added as crushed polycarboxylates and polycarboxylates that are compatible with PLA. Aqueous polycarboxylate superplasticizers, including but not limited to various superplasticizers (e.g., Adva, Plastor, and commercial superplasticizers from BASF, as well as other plasticizers), are excellent carbanogel CNM dispersants, dispersing the crushed carbanogel / polycarboxylate substantially uniformly in the PLA polymer blend by conventional mixing rather than sonication. Thus, both the crushed carbanogel and polycarboxylates can be added prior to PLA polymerization without wasting energy on sonication, providing dispersion of CNMs early through the PLA formation process. In some embodiments of the present disclosure, the fractured carbanogel and / or polycarboxylate are subsequently added to a polymerization process, and then the PLA polymer, fractured carbanogel and / or polycarboxylate undergo an extrusion process to provide a substantially uniform distribution of CNM throughout the PLA polymer. These alternative fractured, unbroken polymer-CNM mixture formation protocols are shown in FIG.

[0067]

[0072] Example 2: Carbanogel PLA polymer-CNT formation conditions by extrusion

[0068]

[0073] In a further embodiment of the present disclosure, polymer-CNM blends are prepared using crushed carbanogel particles instead of conventionally dispersed CNM during the polymer extrusion step. Extrusion may utilize blending the processed carbanogel with either solid or molten polymer. This embodiment is compared to a conventional process for PLA-CNT blend preparation, in which 0, 2, 4, 6 or 8 wt% CNTs are blended with PLA pellets by blending for 8 hours. Sonication, which delivers ultrasonic energy without liquid, is not possible in this medium. The extension of blending time by blending is an attempt to achieve uniform dispersion despite the absence of sonication. The known extrusion process uses a twin screw extruder followed by a single screw extruder, with the temperature increased from 165°C to 220°C to form known PLA / CNT blends for testing. 6 wt% CNT addition showed the greatest strength increase. Compared to PLA with 0% CNT, the 6 wt% PLA / CNT blends showed a 64% increase in tensile strength and a 29% increase in bending strength. Instead of conventional CNTs, in this embodiment of the present disclosure, treated carbanogel was added with PLA during mixing for extrusion. Thus, a comparable PLA-CNT strength increase can be achieved with substantially the same CNT loading using a much lower mixing time, such as less than an hour. According to an embodiment of the present disclosure, mixing the molten polymer with carbanogel causes a significant increase in the associated storage modulus.

[0069]

[0074] Example 3: Thermosetting resin-carbanogel mixture

[0070]

[0075] This example relates to forming a polymer-CNM mixture through combining the treated carbanogel with a thermosetting resin that generally cannot be dissolved and reformed, such as an epoxy. The treated carbanogel may be a crushed carbanogel, which may improve dispersion and interaction with the polymer. For example, in one type of conventional epoxy-CNT mixture, the CNTs are uniformly dispersed (as opposed to the carbanogel) and then covalently bonded to an epoxide (cyclic or O bonded to two C) containing moiety via amine bonds, which then react with the epoxide groups to form the epoxy-CNT mixture. In some embodiments of the present disclosure, the crushed carbanogel is dispersed by mixing in a solvent that is a compatible medium, creating defects and grafting and / or covalently bonding the CNMs to the epoxide (O bonded to two C) via functional group sites. Following this mixing, the epoxide is reacted via chemical reaction (including polyamine, polyamide alkaline or anhydride mediated reactions), thermal based curing agents or photon based curing agents to open the oxygen ring and form an epoxy-CNM mixture formed from crushed carbanogel rather than traditional CNTs.

[0071]

[0076] Further embodiments of the present disclosure utilize blending of CNMs with polymers. This is accomplished by dispersing the CNMs in the polymer mixture, here by directly blending the crushed carbanogel into the polymer mixture. Conventional dispersion of CNMs in the mixture is accomplished by shear mixing, either mechanical or magnetic calendaring, extrusion, ball milling or ultrasonication or combinations thereof, and is used in direct immersion or indirect consolidation to improve fibers.

[0072]

[0077] Example 4: Increased Tensile Strength of Epoxy-CNM Blends

[0073]

[0078] FIG. 4 shows photos and tensile strength dates from examples of epoxy resins with and without the addition of carbanogel made from CO2 according to an embodiment of the present disclosure. The top panel of FIG. 4 shows three items made without carbanogel (three dog-bone items on the left) and three items made with carbanogel according to an embodiment of the present disclosure, the carbanogel items (three dog-bone items on the right). The carbanogel items are generally black and the photos have been lightened to enhance contrast. The carbanogel used to make the carbanogel items was made using an electrolysis process as described herein to convert CO2 to carbanogel. The carbanogel was made in apparatus 10 using a steel stainless steel case 304 in a Li2CO3 dissolved electrolyte at 750° C. with a Muntz brass cathode and stainless steel 304 anode producing a CNT carbanogel product. Carbanogel was also made from CO2 to make CNT carbanogel products when the cathode was changed to Monel or Ni alloys, such as Inconel, Nichrome, and Ni-iron and Ni-copper alloys, and the anode was changed to Inconel, Nichrome, and Ni-iron and Ni-copper alloys. This carbanogel product was cleaned with hydrochloric acid (HCl). About 4 parts of Metlab M135 resin and about 1 part of Metlab M135 hardener were degassed separately inside a vacuum chamber at 60°C. Then, the desired 0 wt%, 0.05 wt%, 0.1 wt%, 0.25 wt%, or 0.5 wt% carbanogel with reduced electrolyte containing purified CNTs was added to the resin, then mixed at 65 rpm for 4 minutes, then sonicated for 15 minutes. After sonication, the hardener was added, mixed at 65 rpm for 4 minutes, then degassed. Samples were cured in a conventional "dog bone" mold at 60°C and removed for tensile strength testing. The top panel of Figure 4 shows three cured control samples with no added carbanogel at the top left and three cured samples with 0.5 wt% carbanogel at the top right. Tensile strength for the control samples was measured on an ETM-10kN computer controlled electronic universal test machine. The bottom panel of Figure 4 shows the observed increase in tensile strength compared to the tensile strength of the items without added carbanogel.The bottom panel of FIG. 4 shows examples of 0.05 wt %, 0.1 wt %, 0.25 wt % and 0.5 wt % carbanogels with measured relative increases of 4%, 15%, 21% and 33%, respectively.

[0074]

[0079] Example 5: Polymer-CNM Blend Alone and Combined with Alternating Layers

[0075]

[0080] The polymer-CNM blends may be used alone in materials or products such as flat backings, flame retardants, or heat shields. The polymer-CNM blends may also be used in combination with other materials not made from the polymer-CNM blends, such as, but not limited to, laminates, where the polymer-CNM blends impart new or improved properties to the other materials. For example, the polymer-CNM blends and composites thereof exhibit shape memory properties under various activation conditions, such as thermal activation, mechanical activation, electrical activation, magnetic activation, photoactivity, or chemical activation. This shape memory property may be incorporated into the polymer-CNM blends, materials, or products made therefrom, as well as materials or products made from combinations of the polymer-CNM blends (or materials or products thereof) and another material. In addition to the shape memory properties, when epoxy is used as the polymer in the polymer-CNM blends, the tensile strength may increase by up to 184%, and when the CNMs include multi-walled CNTs, the impact strength increases by up to 444% with a 0.1-1 wt% addition, which occurs by selecting the operating conditions of the electrolysis process. Additionally, the operating conditions of the electrolysis process are selected to increase the relative amount of coiled CNTs within the CNMs, which may have an enhanced spring effect. These shape memory properties may also be promoted by incorporating anisotropic properties in the polymer-CNM blends by aligning them, as described above. The electrical and thermal conductivity of CNMs such as graphene may provide superior properties for their application as polymer heating elements or radiators. Incorporating shape memory properties and heating element behavior may each be beneficial alone or in combination with layers of another material.

[0076]

[0081] FIG. 5 is an example of a carbanogel with reduced electrolyte by washing, as measured by scanning electron microscopy, SEM, shown at two different magnifications, 720x and 8600x. This example is of the CNT carbanogel prepared by CO2 electrolysis in the preceding example. The large particle size of the intermingled CNMs containing the carbanogel is evident in the top panel of FIG. 5. This is large compared to conventional filtration media porosity and provides a rare opportunity for nano-dimensional CNMs to be macroscopically handled for blending into polymers. In addition to the advantage of being formed from CO2 rather than high carbon footprint reactants, this allows the carbanogel to be easily formed from fine suppressive filters, despite the nano-material dimensions of the carbanogel material, as shown in the bottom panel of FIG. 5. Following electrolysis, the carbanogel was peeled off from the cooled cathode and crushed. Following washing with concentrated HCl, the processed carbanogel is shown in the SEM image of FIG. 5. The high purity of the CNTs and their orientation in various directions is also evident in FIG. 5. An alternative wash with dilute HCl acid similarly washed away electrolytes and metal impurities as measured by electron dispersive spectroscopy (EDS) and thermogravimetric analysis (TGA). An alternative wash with either water or formic acid primarily only removed excess electrolytes and not metal impurities. Another alternative wash with combined HCl and hydrogen peroxide, in this case ultrasonic dissolution rather than mixing the carbanogel in a solution of concentrated HCl and 35% H2O2, removed excess electrolytes, metal impurities and even amorphous carbon impurities. Similarly, other chemical oxidants, such as hydrochloric acid and potassium permagnate, were observed to be effective at sufficient dilution and electrochemically generated oxidants were generated. Amorphous carbon is more susceptible to oxidation than more robust graphene nanocarbon structures, such as stacked graphene CNT structures, as measured by the lower combustion temperature in TGA of amorphous carbon compared to carbon nanotubes. Thus, amorphous carbon can be removed as an impurity by chemical oxidation, electrochemical oxidation, thermal oxidation, or any combination of these. As a further example of reducing the impurity content of the carbanogel, the carbanogel is heated to 300° C. following an HCl wash.The reduced impurity content was measured by the observed reduced mass of the carbanogel by TGA and SEM after the impurity reduction step. The TGA data showed that the HCl and heating steps largely removed the amorphous carbon impurities, and the SEM analysis showed that the reduced impurity content carbanogel retained the CNTs.

[0077]

[0082] Without being limited by any particular theory, the polymer-CNM blends of the present disclosure may be used in polymer material and polymer product applications where (i) the carbanogel content provides improved strength and / or conductivity, thereby reducing the input materials required to make the polymer material or polymer product; (ii) the polymer material and polymer product can last longer through improved chemical, mechanical, optical and thermal resistance, while still being as recyclable as currently available polymer materials and products made without the carbanogel of the present disclosure; (iii) the polymer-CNM blends of the present disclosure replace less environmentally friendly polymers, such as polyethylene, with the polymer-CNM blends of the present disclosure, such as PLA-CNM blends; (iv) the polymer material and polymer product applications act as carbon sequestration reservoirs, thereby increasing the environmental sustainability of such polymer materials and polymer products made therefrom, or any combination thereof.

[0078]

[0083] CNM-polymer blends made according to embodiments of the present disclosure may be used in a variety of material and product applications, including, but not limited to, backings, flame retardants, or shielding. However, polymer-CNM blends according to embodiments of the present disclosure, materials, and products made therefrom may also be used as components of composite materials, such as, but not limited to, laminates that include at least one layer made from a polymer-CNM blend with other non-CNM materials, imparting enhanced properties to those other non-polymer materials. Furthermore, polymers made from polymer-CNM blends and composites made with such polymers (including CNM) exhibit shape memory properties under thermal, mechanical, electrical, magnetic, optical, or chemically active conditions, and these properties may be imparted to materials or products that include CNM (by impregnation, or reinforcement, or alternatively integration) such as containing polymers. This shape memory effect is facilitated by the inclusion of anisotropic properties in the polymers made from the polymer-CNM blends, as described above. Furthermore, the electrical and thermal conductivity of CNM-polymer products may provide superior properties when used in heating element or radiator applications.

[0079]

[0084] Other applications of materials and products made from the polymer-CNM blends of the present disclosure that can particularly take advantage of the superior CNM properties imparted by the carbanogel include, but are not limited to, (i) light-weight tooling applications for high speed, safety and rapid changeovers, (ii) harder tools for better drilling, impact and / or sawing, (iii) tools with better thermal management, (iv) super-strong and foldable materials, (v) general sequestration of CO2, (vi) super-lightweight, super-absorbent sponges, (vii) as pre-made laminate sheets for inclusion within composites, (viii) ballistic or electromagnetic field (EMF) shielding, (ix) parachutes and drag enhancers, (x) knittable / sewable polymers for fabrics / textiles, or (xi) fibers / threads for 3D manufacturing or printing.

[0080]

[0085] Other uses of materials and products made using polymer-CNM blends according to embodiments of the present disclosure include products that combine the benefits of two or more superior CNM-based properties, such as structural materials that provide dual uses that additionally reduce weight, material cost / material used, and / or increase capacity. Some non-limiting examples of such dual uses include: (i) using strength properties for structural purposes and using electrical energy storage properties, (ii) using strength properties for structural purposes and using thermal energy storage properties, (iii) using strength properties for structural purposes and using as electrical conduits or wires, (iv) using strength properties for structural purposes and using as sensors to collect real-time strain or safety data to evaluate material performance, (v) using strength properties for structural purposes and using as catalysts, (vi) using strength properties for structural purposes and using as thermal conduits, or any combination thereof. There are also applications and uses of materials and products made using polymer-CNM blends according to embodiments of the present disclosure for use in heat dissipation members to dissipate high heat in applications where fire is a concern, thereby increasing safety.

Claims

1. 1. A method for preparing a polymer-carbon nanomaterial (CNM) blend, comprising: (a) receiving a carbanogel product, the carbanogel product comprising a network of CNMs dispersed in an electrolyte; (b) combining the carbanogel product with a polymer mixture; (c) collecting the polymer-CNM mixture; The method includes:

2. Carbon Dioxide (CO 2 2. The method of claim 1, further comprising generating the carbanogel product by a melt electrolysis process to partition the CNM and an electrolyte, the carbanogel product comprising CNM and an electrolyte.

3. The method of claim 1 further comprising a preparation step for preparing the polymer mixture.

4. 4. The method of claim 3, wherein the polymer mixture comprises one or more polymer precursors, and the preparing step occurs after the step of combining the carbanogel product with the polymer mixture.

5. The method of claim 3 , wherein the preparing step occurs prior to the step of combining the carbanogel product with the polymer mixture.

6. 6. The method of claim 5, further comprising the step of extruding the combined carbanogel product and polymer mixture.

7. 10. The method of claim 1, further comprising the step of treating said carbanogel product prior to said step of combining said carbanogel product with said polymer mixture.

8. 8. The method of claim 7, wherein the step of processing the carbanogel product comprises grinding, comminuting, pressing, pulverizing, milling, crushing, or combinations thereof.

9. 10. The method of claim 1 further comprising reducing the electrolyte content of the carbanogel product.

10. 10. The method of claim 9, wherein the reducing step comprises pressing, reacting, washing, filtering, or any combination thereof.

11. 10. The method of claim 1, further comprising the step of applying heat after said step of receiving said carbanogel product, said heat being at a temperature of from about 0°C to about 1000°C.

12. The method of claim 1 , wherein the polymer mixture is prepared by a condensation mechanism, a ring-opening mechanism, an ionic mechanism, a chain transfer photon mechanism, a thermal mechanism, a chemical mechanism, a plasma polymerization mechanism, or any combination thereof.

13. The method of claim 1 , wherein the polymer-CNM mixture comprises from 10% by weight CNM to less than 10% by weight CNM.

14. 10. The method of claim 1, wherein the carbanogel product comprises an entangled product of CNM.

15. 10. The method of claim 1, wherein the received carbanogel product comprises CNMs including spherical nanocarbons, solid nano-onions, hollow nano-onions, cylindrical allotropic nanocarbons, planar allotropic nanocarbons, helical allotropic nanocarbons, carbon nanotubes (CNTs), nanofibers, graphene, nanoplatelets, nanoscaffolds, nanotrees, nanobelts, nanoflowers, nanodragons, nanorods, surface modified or metal coated CNMs, featureless amorphous nanocarbons, or any combination thereof.

16. The method of claim 1 , wherein the polymer mixture comprises natural polymers, synthetic polymers, semi-synthetic polymers, regenerated polymers, or any combination thereof.

17. The method of claim 1 , wherein the polymer mixture comprises an amorphous polymer, a semi-crystalline polymer, or any combination thereof.

18. The method of claim 1 , wherein the polymer mixture comprises a thermoset polymer, a thermoplastic polymer, or any combination thereof.

19. 10. The method of claim 1, wherein the polymer blend comprises at least one of PLA, PVA, PP, PE, acrylic, ABS, nylon, Teflon, PC, epoxy, acrylic, phenolic, polysiloxane, polyurethane, polyimide, vulcanized rubber, bakelite, polydicyclopentadiene, polyisocyanurate, polyester, polyurea, urea formaldehyde, vinyl ester, cyanate, melamine, polyester resin, or any combination thereof.

20. The method of claim 1 further comprising the step of applying an alignment force to the carbanogel product.

21. 21. The method of claim 20, wherein the aligning force is applied by one or more of a mechanical force, an electric current, a magnetic field, or any combination thereof.

22. 21. The method of claim 20, wherein the aligning force is of a linear, radial, cylindrical, spherical or other shape to produce a linear, radial, cylindrical, spherical or other directional shape to produce one or more anisotropic characteristic properties of the polymer-CNM mixture.

23. 10. The method of claim 1, further comprising applying a void-filling agent to partially or substantially completely fill voids in the polymer-CNM mixture, on the surfaces of the CNMs of the mixture, within the interior spaces of the CNMs of the mixture, or any combination thereof.

24. 24. The method of claim 23, wherein the void-filling agent is a strengthening agent, a catalyst, a dopant, a magnetic material, a drug, an electromagnetic force shielding enhancement agent, or any combination thereof.

25. 25. The method of claim 24, wherein the toughening agent comprises an epoxy, a resin, another polymer, a copolymer, a cementitious material, a metal, an alloy, or any combination thereof.

26. 25. The method of claim 24, wherein the catalyst comprises an epoxy, a resin, another polymer, a copolymer, a cementitious material, a metal, an alloy, or any combination thereof.

27. 25. The method of claim 24, wherein the dopants comprise boron, nitrogen, sulfur, phosphorus, cobalt, aluminum, silicon, cerium, platinum, gold, ruthenium, osmium, tellurium, tungsten, oxides of the respective, salts of the respective, or any combination thereof.

28. 25. The method of claim 24, wherein the magnetic material is iron, nickel, cobalt, gadolinium, samarium, neodymium, steel, carbides of each, other alloys including one or more magnetic materials with ferromagnetic, paramagnetic, diamagnetic properties, or any combination thereof.

Citation Information

Patent Citations

  • Use of carbon nanomaterials produced with low carbon footprint to produce composites with low co 2 emission

    WO2020092449A1